2004
DOI: 10.1016/j.bbamem.2004.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Hexadecylphosphocholine interaction with lipid monolayers

Abstract: The phospholipid analogue miltefosine or hexadecylphosphocholine (HePC) is a drug of high interest in the treatment for fatal visceral leishmaniasis (VL) due to Leishmania donovani particularly because of its activity by oral route. In this study, the interaction of HePC with a monolayer of beta-palmitoyl-gamma-oleyl-phosphatidylcholine (POPC) as membrane model or sterol (ergosterol or cholesterol) was investigated. At a constant pressure of 25 mN/m, the adsorption kinetics of HePC into the monolayers showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
60
0
6

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 30 publications
15
60
0
6
Order By: Relevance
“…We can conclude from the above experiment that analkylphospholipid-like molecule can easily exchange between membranes and can accumulate in cells when they are in contact with liposomal OPP formulations. This is in agreement with lipid monolayer experiments, which showed that alkylphospholipids, below the critical micellar concentration (CMC), insert progressively into lipid monolayers as monomers from the aqueous medium, while above CMC, not only monomers but also groups of monomers (micelles) are transferred into the monolayers (Rakotomanga et al, 2004). It was also shown that, while the alkylphospholipid HePC is miscible with POPC, there is high affinity between HePC and sterols (ergosterol, and cholesterol) and that maximum condensation is reached at a ratio of HePC/sterol around 50:50 (mol/mol) (Rakotomanga et al, 2004).…”
Section: Transport Of Spin Labeled Perifosine (Opp) From Liposomes Tosupporting
confidence: 73%
See 4 more Smart Citations
“…We can conclude from the above experiment that analkylphospholipid-like molecule can easily exchange between membranes and can accumulate in cells when they are in contact with liposomal OPP formulations. This is in agreement with lipid monolayer experiments, which showed that alkylphospholipids, below the critical micellar concentration (CMC), insert progressively into lipid monolayers as monomers from the aqueous medium, while above CMC, not only monomers but also groups of monomers (micelles) are transferred into the monolayers (Rakotomanga et al, 2004). It was also shown that, while the alkylphospholipid HePC is miscible with POPC, there is high affinity between HePC and sterols (ergosterol, and cholesterol) and that maximum condensation is reached at a ratio of HePC/sterol around 50:50 (mol/mol) (Rakotomanga et al, 2004).…”
Section: Transport Of Spin Labeled Perifosine (Opp) From Liposomes Tosupporting
confidence: 73%
“…This is in agreement with lipid monolayer experiments, which showed that alkylphospholipids, below the critical micellar concentration (CMC), insert progressively into lipid monolayers as monomers from the aqueous medium, while above CMC, not only monomers but also groups of monomers (micelles) are transferred into the monolayers (Rakotomanga et al, 2004). It was also shown that, while the alkylphospholipid HePC is miscible with POPC, there is high affinity between HePC and sterols (ergosterol, and cholesterol) and that maximum condensation is reached at a ratio of HePC/sterol around 50:50 (mol/mol) (Rakotomanga et al, 2004). This kind of behavior is generally known as the condensing effect of cholesterol towards phospholipids (Chapman et al, 1969;Ghosh & Tinoco, 1972).…”
Section: Transport Of Spin Labeled Perifosine (Opp) From Liposomes Tosupporting
confidence: 73%
See 3 more Smart Citations